Design and mechanical analysis of a novel modular bionic earthworm robot with upright functionality - Shufeng Tang; Jianan Yao; Yue Yu (Scientific Reports)
Abstract With the escalating demand for exploration within confined spaces, bionic design methodologies have attracted considerable attention from researchers, primarily due to the intrinsic limitations of human access to hazardous environments. However, contemporary bionic robots primarily attain linear motion through the axial radial deformation of their body segments, thereby lacking the upright functionality that is characteristic of these organisms. In response to the limitations associated with current bionic earthworm robots concerning upright capability and stiffness modulation, we propose an innovative bionic robot that incorporates upright functionality and programmable stiffness. Initially, we present a bionic robot unit module that is capable of attaining an upright posture. A mechanical model is established in accordance with the principle of minimum potential energy to facilitate various compression and deflection functionalities. Through comprehensive simulation and experimental studies, we validate the model’s high precision in predicting compression and deformation behaviors. Furthermore, the effects of varying spring stiffness values (k) on device performance are systematically investigated, thereby enabling tailored stiffness adjustments for each module. This programmability empowers the robot to adapt to a broader spectrum of environmental demands. Ultimately, we construct a multi-module robot and successfully evaluate its upright functionality under diverse compression and deformation conditions. The proposed bionic structure, characterized by its enhanced ease of control and programmable stiffness, exhibits considerable potential for applications in complex and unstructured environments.